Naldemedine: A New Option for OIBD - Coluzzi F; Scerpa MS; Pergolizzi J (Journal of Pain Research, 2020)
Flaminia Coluzzi,1 Maria Sole Scerpa,1 Joseph Pergolizzi2 1Department of Medical and Surgical Sciences and Biotechnologies, Sapienza University of Rome, Polo Pontino, Latina, Italy; 2NEMA Research Inc., Naples, FL, USACorrespondence: Flaminia ColuzziDepartment of Medical and Surgical Sciences and Biotechnologies, Sapienza University of Rome, Polo Pontino, Corso della Repubblica 79, Latina 04100, ItalyTel +39 0773 6553334Email flaminia.coluzzi@uniroma1.itAbstract: Opioid-induced bowel dysfunction (OIBD) is a common complication in long-term opioid users and abusers. It is a burdensome condition, which significantly limits quality of life and is associated with increasing health costs. OIBD affects up to 60% of patients with chronic non-cancer pain and over 80% of patients suffering from cancer pain and is one of the conditions of the most common symptoms associated with opioid maintenance. Given the continued use of opioids for chronic pain management in appropriate patients, OIBD is likely to persist in clinical practice in the coming years. We will herein review its underlying pathophysiological mechanisms and the available treatments. In the last years, pharmaceutical research has focused on the opportunity of targeting peripheral mu-opioid receptors without affecting their analgesic activity in the central nervous system, and several peripherally acting mu-opioid receptors antagonists (PAMORAs) drugs have been approved. We will mainly focus on naldemedine, discussing its pharmacological properties, its clinical efficacy and side effects. Head-to-head comparisons between naldemedine and the other PAMORAs are not available yet, but some considerations will be discussed based on the pharmacological and clinical data. As a whole, the available data suggest that naldemedine is a valid treatment option for OIBD, as it is a well-tolerated drug that alleviates constipation without affecting analgesia or causing symptoms of opioid withdrawal.Keywords: PAMORAs, opioid-induced constipation, naldemedine, opioid-induced bowel dysfunction, analgesia, chronic pain